Incidence and Characteristics of Pulmonary Embolism in Taiwanese Patients: Impact of Active Malignancy from a 5-year Single Center Experience - 李俊毅(Chun-Yi Li); 余垣斌(Yuan-Bin Yu) (童綜合醫學雜誌, 2011)
Introduction: Cancer patients have increased risk of venous thromboembolism (VTE) and experience more adverse outcome in the treatment of VTE. Pulmonary embolism (PE) particularly could be fatal and contributes significantly to the morbidity and mortality. However, the characteristics and impact of cancer in PE patients are scarcely reported from Oriental societies.Aims: To assess the incidence and clinical characteristics of patients with PE in Taiwan and investigate the impact of active malignancy.Methods: Patients with confirmed diagnosis of PE were retrieved from the hospitalization database of Taipei Veterans General Hospital between January 2004 and December 2008. Clinical characteristics and treatment outcome of cancer and non-cancer patients were recorded via medical chart review and compared using statistical analysis as appropriate.Results: Totally 161 patients with PE were identified and 51 (31.7%) of them had a diagnosis of active cancer. Estimated incidence of PE was 9.8/100,000 per patient-year. Median age was 73.2 years (range 23-94). Ninety-one (56.5%) patients were presented with PE over bilateral pulmonary arteries and concurrent deep vein thrombosis was detected in 28.0% of patients. Lung cancer was the most common subtype (35.3%) in PE patients with cancer, followed by prostate (11.8%), ovarian (9.8%), and hepatocellular (9.8%) histologies. Recurrent VTE rate was higher in cancer group (23.5% vs 9.1%, P=0.013) and major bleeding was more often encountered in cancer patients as well (23.5% vs 4.5%, P＜0.001). By logistic regression analysis, hazard ratio of cancer patients for VTE recurrence and major bleeding was 3.30 (95% confidence interval [CI], 1.24-8.77, P=0.017) and 6.47 (95% CI, 1.9-22.0, P=0.003) respectively. Furthermore, 100-day survival after PE was also inferior in cancer patients. (68.4% vs 89.8%, P=0.001)Conclusion: In contrast to Western countries, incidence of PE is lower in Taiwanese patients. However, cancer remains a major factor influencing the outcome of PE.